Surface roughness differences of bis-acryl provisional crown material under different toothbrush filament and toothpaste abrasive degree: a laboratory experimental study - Aritonang, Halimatutsahdia; Andryas, Ika; Wahyuni, Siti (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Brushing of provisional crown material using a toothbrush and abrasive toothpaste induces surface roughness. This study, therefore, aims to determine the difference in surface roughness on provisional crown materials after brushing with soft and medium filament toothbrushes using high and low abrasive toothpaste. Methods: This type of laboratory experimental research employed a pre-test and post-test group design of 40 samples divided into four groups of ten samples each. The groups consisted of Group A (bis-acrylic temporary crown material brushed with medium-filament toothbrush and high-abrasive toothpaste), Group B (bis-acrylic temporary crown material brushed with soft-filament toothbrush and high-abrasive toothpaste), Group C (bis-acrylic temporary crown material brushed with medium-filament toothbrush and low-abrasive toothpaste), and Group D (bis-acrylic temporary crown material brushed with soft-filament toothbrush and low-abrasive toothpaste). The sample brushing method was carried out using a Modified V8-Brushing Machine tool for 2000 cycles at a speed of 120 cycles/minute and a 0.2 N pressure. Results: A profilometer was used to measure surface roughness. The mean value of surface roughness was analyzed by a univariate test, yielding groups A (0.41 µm ± 0.18), B (0.36 µm ± 0.13), C (0.40 µm ± 0.15), and D (0.25 µm ± 0.09). The Kruskal-Wallis Statistical analysis test determined significant differences among test groups. This study indicates that the surface roughness of bis-acryl provisional crown material brushed with soft and medium-filament toothbrushes differed from that with a combination of high and low-abrasive toothpaste p = 0.001 (p < 0.05). Conclusion: Brushing provisional crown materials with a medium-filament toothbrush resulted in a higher roughness value than with a soft-filament toothbrush, and the group that brushed with high-abrasive toothpaste showed higher roughness values than that with low-abrasive toothpaste.